Current Population Survey, December 2011: Food Security Supplement ([Verlag nicht ermittelbar], 2013)
This data collection is comprised of responses from two sets of survey questionnaires, the basic Current Population Survey (CPS) and a survey on the topic of Food Security in the United States, which was administered as a supplement to the December 2011 CPS questionnaire. The CPS Food Security supplement was sponsored and conducted by the United States Census Bureau for the Economic Research Service (ERS) of the United States Department of Agriculture (USDA). The CPS, administered monthly, is a labor force survey providing current estimates of the economic status and activities of the population of the United States. Specifically, the CPS provides estimates of total employment (both farm and nonfarm), nonfarm self-employed persons, domestics, and unpaid helpers in nonfarm family enterprises, wage and salaried employees, and estimates of total unemployment. Data from the CPS are provided for the week prior to the survey. In December, the week containing the twelfth day of the month was the interview week. The week containing the fifth day was the reference week (i.e., the week about which the labor force questions were asked). The supplement was intended to research the full range of severity of food insecurity as experienced in United States households. Food Security supplement items were used by the supplement sponsor to produce a scaled measure of food insecurity. Therefore, responses to individual items should not be used as meaningful measures of food insufficiency, food insecurity, or hunger. Measures that combine information from multiple items (HRFS12M1 and following) are generally considered to be more reliable measures of food security and food insecurity. The food security questions were asked of all interviewed households, as appropriate. Respondents were queried on how much the household spent for food, their use of federal and community food assistance programs, food sufficiency, and ways of coping with not having enough food. Demographic variables include age, sex, race, Hispanic origin, marital status, veteran status, educational attainment, occupation, and income.